The Effect of Problem Based Learning (PBL) Model on Akidah Akhlak Learning on the Religious Moderation Attitude of MAN IC Central Bengkulu Students - Imam Ghozali; Alfauzan Amin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: This study aims to analyze the impact of implementing the Problem-Based Learning (PBL) model on fostering religious moderation attitudes among class XI students at MAN IC Bengkulu Tengah. Methodology: The research employs a quantitative approach with a sample of class XI students at MAN IC Bengkulu Tengah. Data were analyzed using the Spearman Rank correlation to determine the relationship between PBL implementation and students' religious moderation attitudes. Observations, pretests, and posttests were conducted to support data reliability and validity. Main Findings: The results demonstrate that the PBL model significantly contributes to developing religious moderation attitudes, with a 92% improvement observed among the participants. Through active engagement in problem-solving, students enhanced their critical thinking and analytical skills, enabling them to apply balanced and moderate perspectives in religious and social contexts. The study highlights that integrating real-world issues into Akidah Akhlak lessons through PBL effectively encourages students to embrace diversity and avoid radical tendencies. Novelty/Originality of the Study: This research pioneers the application of PBL in Islamic education, particularly in fostering religious moderation, a critical value in pluralistic societies. It addresses a significant gap in the literature by offering evidence-based insights into the role of innovative pedagogical models in shaping attitudes aligned with inclusivity and tolerance. The study also underscores the potential of PBL to modernize Islamic education by bridging theoretical knowledge with practical, real-world applications, thereby advancing students' holistic character development.